Campaigns of knowledge U.S. pedagogies of colonialism and occupation in the Philippines and Japan - Schueller, Malini Johar 1957- (Ateneo de Manila University Press, 2021)
The creation of a new school system in the Philippines in 1898 and educational reforms in occupied Japan, both with stated goals of democratization, speaks to a singular vision of America as savior, following its politics of violence with benevolent recuperation. The pedagogy of recovery—in which schooling was central and natives were forced to accept empire through education—might have shown how Americans could be good occupiers, but it also created projects of Orientalist racial management: Filipinos had to be educated and civilized, while the Japanese had to be reeducated and “de-civilized.”